Voting Experiences, Perceptions of Fraud, and Voter Confidence. (26th March 2021) - Alvarez, R. Michael; Cao, Jian; Li, Yimeng
Abstract : Objective: Assuring voter confidence is important for the legitimacy of democratic elections. In this article, we test four hypotheses about the correlates of voter confidence at various levels of election administration. Methods: We take advantage of a large online survey of registered voters in a single election jurisdiction, Orange County (CA), which was implemented immediately after the November 2018 midterm elections. We measure voting experience and social media usage using item response theory as well as voters' perceptions of various election or voter fraud, and estimate their association with voter confidence via logistic regression models. Results: Our results show that voters who cast mail ballots are less confident about their own votes being counted correctly than in‐person voters. For both types of voters, those who have poor experiences with the voting process are much less likely to report confidence in the election. We also find that voters who have strong concerns about election fraud are less likely to report being confident in the election. Our last result indicates that information from news and social media is associated with a decline in voter confidence in election administration at the national level. Conclusion: Given the many conversations about election fraud that have occurred since the 2016 presidential election, this research provides important implications for election administration in future elections in the United States.